2019
DOI: 10.3390/ma12132078
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ultraviolet Photofunctionalization on a Titanium Dental Implant with Machined Surface: An In Vitro and In Vivo Study

Abstract: Ultraviolet (UV) photofunctionalization has been suggested as an effective method to enhance the osseointegration of titanium surface. In this study, machined surface treated with UV light (M + UV) was compared to sandblasted, large-grit, acid-etched (SLA) surface through in vitro and in vivo studies. Groups of titanium specimens were defined as machined (M), SLA, and M + UV for the disc type, and M + UV and SLA for the implant. The discs and implants were assessed using scanning electron microscopy, confocal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 44 publications
(59 reference statements)
1
34
0
Order By: Relevance
“…All implants placed in tibias and femurs were unloaded. In detail, most authors reported significantly increased BIC [57,71,[73][74][75][76][77][78][79], push-in values [40,44,[80][81][82][83], bone volume [72,84], or bone mineral [85,86] were noted in all animal models studied for photofunctionalized groups disregarding implant surface modifications/topography. The differences were insignificant for both UV-treated and non-UV-treated reported in four animal studies [87][88][89][90].…”
Section: Resultsmentioning
confidence: 99%
“…All implants placed in tibias and femurs were unloaded. In detail, most authors reported significantly increased BIC [57,71,[73][74][75][76][77][78][79], push-in values [40,44,[80][81][82][83], bone volume [72,84], or bone mineral [85,86] were noted in all animal models studied for photofunctionalized groups disregarding implant surface modifications/topography. The differences were insignificant for both UV-treated and non-UV-treated reported in four animal studies [87][88][89][90].…”
Section: Resultsmentioning
confidence: 99%
“…UV-mediated photofunctionalization induces a conversion of the surface wettability to a more hydrophilic status and a modification of the surface electrostatic properties by the removal of hydrocarbons (Dini et al, 2020;Hori et al, 2010). These surface modifications have been proven to increase protein adsorption and osteoblastic cell adhesion and, consequently, to accelerate the osseointegration process in in vitro and in vivo conditions (Aita et al, 2009;de Avila et al, 2015;Choi et al, 2017;Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This includes hydrocarbon removal, electropositive status conversion, and surface superhydrophilicity produced by the creation of oxygen vacancies (Aita et al, 2009). These surface modifications have demonstrated significant improvements in the biological properties of dental implants with greater protein adsorption as well as higher proliferation, differentiation, and mineralization of osteogenic cells in vitro (Att et al, 2009;Lee et al, 2019;Minamikawa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…UV photofunctionalization has been extensively studied in vitro and in vivo in the last decade as surface modification of implantable metallic materials (Areid et al, 2018;Henningsen et al, 2018;Soltanzadeh et al, 2017). This phenomenon has been found to be associated with the photochemical and photocatalytic removal of hydrocarbons from the metallic surfaces, and it has been suggested as an effective method of enhancing the osteoconductivity to improve the F I G U R E 4 Scheme of histological sectioning showing the cut orientation osseointegration and bone formation (Lee et al, 2019;Yamauchi et al, 2017), similar to that seen for non-thermal plasma treatment and nano-scaled surface modification (Guo et al, 2019;Henningsen et al, 2018;Wang et al, 2018). The treatment has proven to be effective in enhancing bone formation and bone regeneration in the treatment of critical bone defects; but, it has been mainly used in dentistry (Hirakawa et al, 2013;Park, Koak, Kim, Han, & Heo, 2013;Suzuki, Kobayashi, & Ogawa, 2013).…”
Section: Discussionmentioning
confidence: 99%